2013
DOI: 10.1186/1751-0147-55-82
|View full text |Cite
|
Sign up to set email alerts
|

Variation of serum selenium concentrations in German sheep flocks and implications for herd health management consultancy

Abstract: BackgroundThis study was performed to demonstrate the widespread distribution and severity of selenium (Se) deficiency in sheep flocks and to evaluate the impact of influencing factors. In 150 flocks, ten serum samples of adult ewes were analysed for Se concentration. The farmers were interviewed concerning flock size, provision of mineral supplement, predominant form of husbandry (stationary fenced pasture/transhumance), predominant form of water provision (tap water/well/surface water) and predominant soil (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Similar results were reported by Kurt et al (2001), who observed that blood Se levels of Akkaraman sheep in the Diyarbakır region (southeast of Anatolia) were 46-65 ng/mL. These results are similar to the findings reported by Kurt et al (2001) in the current trial, although the results of these authors were higher than those seen in a Polish research, in which the serum Se level of sheep was 31 ng/mL (Pılarczyk et al, 2004), or the Iranian trial with 28 ng/mL (Karimi-Poor et al, 2011), or the German trial, which showed 45 ng/mL (Humann-Ziehank et al, 2013). Øvernes et al (1985) reported that plasma Se concentration of sheep should be 150-350 ng/mL, as white muscle disease is seen when it is below 100 ng/mL.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were reported by Kurt et al (2001), who observed that blood Se levels of Akkaraman sheep in the Diyarbakır region (southeast of Anatolia) were 46-65 ng/mL. These results are similar to the findings reported by Kurt et al (2001) in the current trial, although the results of these authors were higher than those seen in a Polish research, in which the serum Se level of sheep was 31 ng/mL (Pılarczyk et al, 2004), or the Iranian trial with 28 ng/mL (Karimi-Poor et al, 2011), or the German trial, which showed 45 ng/mL (Humann-Ziehank et al, 2013). Øvernes et al (1985) reported that plasma Se concentration of sheep should be 150-350 ng/mL, as white muscle disease is seen when it is below 100 ng/mL.…”
Section: Discussionsupporting
confidence: 91%
“…Serum Se levels of 25–50 μg/L are considered insufficient, while the optimal value falls between 120 and 150 μg/L [ 39 ]. Low concentrations of this microelement were also noted in sheep by Humann-Ziehank et al [ 40 ] and Milewski et al [ 30 ], who reported an average serum Se level of 45.4 and 48.70 µg/L, respectively. Much lower results were obtained by Pilarczyk et al [ 41 ] and Karimi-Poor et al [ 42 ], 13 µg/L and 28 µg/L, respectively.…”
Section: Discussionsupporting
confidence: 55%
“…Subsequently, a nation-wide survey on farmed sheep revealed more than one third of the German sheep flocks showing Se deficiency. The intra-group range of serum Se concentration varied enormously, the main factors for low Se status were large flocks, shepherding/transhumance and outdoor seasons leading to the suspicion of a high impact of the nutritional management to ensure mineral supplementation of all individuals consistently [95].…”
Section: Selenium Deficiencymentioning
confidence: 99%